-2(y-7)-4=

Simple and best practice solution for -2(y-7)-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(y-7)-4= equation:


Simplifying
-2(y + -7) + -4 = 0

Reorder the terms:
-2(-7 + y) + -4 = 0
(-7 * -2 + y * -2) + -4 = 0
(14 + -2y) + -4 = 0

Reorder the terms:
14 + -4 + -2y = 0

Combine like terms: 14 + -4 = 10
10 + -2y = 0

Solving
10 + -2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -2y = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -2y = 0 + -10
-2y = 0 + -10

Combine like terms: 0 + -10 = -10
-2y = -10

Divide each side by '-2'.
y = 5

Simplifying
y = 5

See similar equations:

| 13x+5(3-5x)= | | -3(5s-6)-18=-3(9s+2)-3 | | -(3x+4)-(-2x-6)=13 | | a^2=0.5 | | 2(t-6)+6t=4(2t+3)-8 | | 5.3q-4.9-6.7q=-2.7-1.4q-2.2 | | 7(x-4)+7=2x+5(-4+x) | | 8g+1=15g-6 | | log[2](3*10x-22)=3 | | log[2]((3)(10x)-22)=3 | | 2x+p-7x+2p= | | (2x+y)+(3x+y)= | | 20+(-3)=17 | | 28+a=-16 | | 4x-7=17+7x | | 0.007x^2+0.02x=150 | | 3(2x-5)=5x-26 | | 14x=-19 | | 2a-3b+4a-b+6a+4b=180 | | -20p(3p-2)(3p-2)-20(3p-2)p-5p=-45p(2p-1)(2p-1) | | 21x^2+25x-56=0 | | 121h^2=225 | | X^3-14x+24=0 | | -2(4x)-1=4x | | 36000*x=7200*x*x | | 25w^2-144=0 | | X^3-14x^2+24=0 | | 31x+x^4=-1 | | 31x+x^4= | | 20x+15y=3175 | | 2(x-5)-5=4x-2(5+x) | | x^4-2ax^3+a^3x=0 |

Equations solver categories